Hubungan Kesediaan Masyarakat Mengikuti Vaksin Covid-19 Dilihat dari Aspek Tingkat Pengetahuan di Wilayah Ungaran: The Relationship of Public Willingness to Participate in the Covid-19 Vaccine Viewed from the Level of Knowledge in the Ungaran Region - Niken Dyahariesti; Rachmawati Eka Putri; Hasna Mawar Halimah (Journal of Holistics and Health Sciences (JHHS), 2022)
Vaccines are biological products that contain antigens which if given to humans will actively develop special immunity against certain diseases. Covid-19 is a disease caused by SARS-CoV-2 and is now an epidemic throughout the world, one of the ways to prevent transmission and increase the outbreak is to carry out a Covid-19 vaccine. The public's willingness to vaccinate is needed to support these efforts. This willingness is strongly influenced by the level of knowledge possessed by the community, especially in Ungaran. Therefore, this study aims to determine the relationship between people's willingness to participate in the covid-19 vaccine, seen from the aspect of the level of knowledge in the Ungaran area. This study uses a cross sectional research design, data collection by purposive sampling using a questionnaire on 200 respondents. Data analysis used the Kolmogorov-Smirnov Non-Parametric Test with a 95% confidence level. The results showed that the level of knowledge was 83% good, 15.5% enough and 1.5% less. And 94% of respondents who are willing to be vaccinated, 6% are not willing to be vaccinated, the results of data analysis are the asymp sig value of 0.00 <0.05. So there is a relationship between the level of knowledge and the willingness to participate in the covid-19 vaccine. ABSTRAKVaksin merupakan produk biologi yang mengandung antigen yang jika diberikan kepada manusia akan secara aktif mengembangkan kekebalan khusus terhadap penyakit tertentu. Covid-19 merupakan penyakit yang disebabkan oleh SARS-CoV-2 dan sekarang menjadi wabah diseluruh dunia, salah satu pencegahannya penularan dan bertambahnya wabah tersebut yaitu dengan melakukan vaksin Covid-19. Kesediaan masyarakat untuk melakukan vasksinasi sangat diperlukan untuk mendukung upaya tersebut. Kesediaan ini sangat dipengaruhi oleh tingkat pengetahuan yang dimiliki masyarakat terutama di Ungaran. Maka dari itu penelitian ini bertujuan untuk mengetahui hubungan kesediaan masyarakat dalam mengikuti vaksin covid-19 dilihat dari aspek tingkat pengetahuan di wilayah Ungaran. Penelitian ini menggunakan desain penelitian cross sectional, pengambilan data secara purposive sampling dengan menggunakan kuesioner pada 200 responden. Analisis data menggunakan Uji Non Parametrik Kolmogorov-Smirnov dengan tingkat kepercayaan 95 %. Diperoleh hasil bahwa tingkat pengetahuan baik 83%, cukup 15,5 % dan kurang 1,5 %. Dan responden yang bersedia divaksin 94 %, tidak bersedia divaksin 6 %, hasil analisa data nilai asymp sig 0,00<0,05. Jadi terdapat hubungan tingkat pengetahuan dengan kesediaan mengikuti vaksin covid-19 .